Cooperative Chloride Hydrogel Electrolytes Enabling Ultralow-Temperature Aqueous Zinc Ion Batteries by the Hofmeister Effect - Yan, Changyuan; Wang, Yangyang; Deng, Xianyu; Xu, Yonghang (Nano-Micro Letters, 2022)
Aqueous zinc ion batteries have high potential applicability for energy storage due to their reliable safety, environmental friendliness, and low cost. However, the freezing of aqueous electrolytes limits the normal operation of batteries at low temperatures. Herein, a series of high-performance and low-cost chloride hydrogel electrolytes with high concentrations and low freezing points are developed. The electrochemical windows of the chloride hydrogel electrolytes are enlarged by > 1 V under cryogenic conditions due to the obvious evolution of hydrogen bonds, which highly facilitates the operation of electrolytes at ultralow temperatures, as evidenced by the low-temperature Raman spectroscopy and linear scanning voltammetry. Based on the Hofmeister effect, the hydrogen-bond network of the cooperative chloride hydrogel electrolyte comprising 3 M ZnCl2 and 6 M LiCl can be strongly interrupted, thus exhibiting a sufficient ionic conductivity of 1.14 mS cm−1 and a low activation energy of 0.21 eV at −50 °C. This superior electrolyte endows a polyaniline/Zn battery with a remarkable discharge specific capacity of 96.5 mAh g−1 at −50 °C, while the capacity retention remains 100% after 2000 cycles. These results will broaden the basic understanding of chloride hydrogel electrolytes and provide new insights into the development of ultralow-temperature aqueous batteries. Highlights: 1 The electrochemical windows of the chloride hydrogel electrolytes are enlarged by >1 V under cryogenic conditions. 2 The cells based on electrolytes with high Cl− concentrations can work in more severe environments. 3 Based on the Hofmeister effect, the hydrogen-bond network of the electrolytes can be strongly interrupted by the addition of Li+. 4 The full cell with the optimized hydrogel electrolyte presents impressive electrochemical performance at –50 °C.